2017
DOI: 10.1002/smj.2643
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frictions in Routine Execution on Economies of Scope

Abstract: Research summary:Based on a detailed database of a beverages producer-distributor that expanded its product variety by leveraging its logistic network, we show that product diversification generates economies of scope and also higher operational costs. The result is an inverted-U relationship between variety and productivity: When the firm offers few additional categories, productivity grows, but as the number of categories rises, the costs of executing the operational routines increase rapidly and productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…This friction takes the form of modified work routines, increased communication, and a need to manage interdependencies in the business, all of which can erode productivity. However, the authors found evidence that these operational frictions could be reduced with more worker experience (Brahm et al, 2017).…”
Section: 74mentioning
confidence: 99%
See 2 more Smart Citations
“…This friction takes the form of modified work routines, increased communication, and a need to manage interdependencies in the business, all of which can erode productivity. However, the authors found evidence that these operational frictions could be reduced with more worker experience (Brahm et al, 2017).…”
Section: 74mentioning
confidence: 99%
“…An inverted U-shaped relationship was identified between PC (Herfindahl type index) and productivity (i.e., the natural logarithm of average drop size) in a transportation company (Brahm et al, 2017). One of the mechanisms at play in the study was operational friction, which is created by adding a variety that is dissimilar from the variety currently being offered (e.g., adding a confectionary product line when the company mostly produces beverages).…”
Section: 74mentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of services also requires an expanded view of a venture’s external environment to include additional competitors, suppliers, marketers, distributors, and customers (Vandermerwe and Rada 1988). These changes create the need to learn new roles and relationships, develop communication systems, refine administrative routines, and attract new qualified employees (Aldrich and Auster 1986; Brahm, Tarzijan, and Singer 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The execution of a strategy depends upon the ability of the leadership team to formulate effective plans, build trust, communicate purpose and intent to the employees, create and align systems for execution and track leading and lagging indicators. Brahm, Tarzijan, and Singer (2017) contend that the execution of strategy usually runs into trouble because there is a tension between expansion strategies and the operational routines required to implement them. With initial expansion, the efficiency of operational routines increases, but beyond a threshold, as expansion increases further, the gains from operational routines decline.…”
Section: Business Strategiesmentioning
confidence: 99%